Novel Co-Operation Between Eotaxin and Substance-P in Inducing Eosinophil-Derived Neurotoxin Release - Amr El-Shazly; Takeru Ishikawa (Mediators of Inflammation)
Eosinophils, chemokines, and neuropeptides are thought to play effector roles in the pathogenesis of allergic diseases such as rhinitis. Eotaxin is a novel C-C chemokine with a potent and relatively specific eosinophil chemoattractant activity that binds selectively to CCR3 receptor, however, its activity in inducing eosinophil granules proteins release is poorly characterized. This study was performed to determine whether eotaxin primes eosinophil exocytosis and whether this co-operates with the sensory neuroimmune-axis. In the present communication, we show that 10 ng/ml eotaxin primed normal human eosinophil for exaggerated eosonophil-derived neurotoxin (EDN) release stimulated by 10-8 M Substance-P (SP). This novel priming was blocked by; 7B11 and Herbimycin A (HA), the CCR3 antagonist and the tyrosine kinase inhibitor, respectively. SDS-Page studies showed significant tyrosine phosphorylation of several protein residues induced by 10-8 M SP only after priming with 10 ng/ml eotaxin. These results demonstrate a novel co-operation between eotaxin and SP in inducing eosinophil cytotoxicity, which at least in part involves tyrosine kinases pathway(s).